Influence of TikTok Video Advertisements on Generation Z’s Behavior and Purchase Intention - Araujo, Clarisse Jane; Perater, Kaye Anne; Quicho, Alyanna Marie; Etrata, Antonio (IJOSMAS, 2022)
TikTok, a widely utilized social media platform owned by ByteDance, has become more incorporated into several marketing strategies because of its fast-growing market and engagement reach. With Generation Z users dominating the platform, content creation for short-form videos mainly aims to get their attention and awareness. This study identified what influences the behavior and perception of users when exposed to emotional, entertaining, and informative TikTok advertisements and examined how these affect the associations they form with the videos in regards to their purchase intention. The researchers sought to gather the data needed with an online survey questionnaire wherein a purposive sampling method was used to determine 386 male and female TikTok users, aged 18-24 years old, residing in Metro Manila, Philippines. The data analysis was done in a quantitative manner with a descriptive-correlational design and statistical tool, Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings have shown that emotional, entertaining, and informative dimensions of TikTok video advertisements positively affect consumer behavior. However, only the emotional dimension positively affects purchase intention out of the three dimensions. Further, this study discovered that Generation Z’s consumer behavior significantly impacts their purchase intention. Data from this research can aid students, professors, marketers, and advertising agencies understand the customers' behavior towards TikTok and learn how they can use it as leverage for further improvement of strategies in addressing the customers' needs.